Overview of the Use of Eye-Tracking Technology for Monitoring Consumer Views - Peša Anita; Valčić Marko; Smokrović Ana Maria; Laura Izabela (Naše gospodarstvo/Our economy, 2024)
Eye-tracking technology has become increasingly popular in studying consumer behavior and decision-making as a part of the marketing research area. The paper highlights the importance of eye tracking in the study of consumer behavior including the use of eye tracking in virtual reality environments, the integration of eye tracking with other physiological measures, and the development of more sophisticated analytical techniques. By observing eye movements and fixations researchers can gain insight into the visual and cognitive processes underlying consumer choices. For this reason, a literature review of relevant studies provides a detailed synthesis of the development of eye-tracking experiments. This apaper contributes to the latest findings on consumer behavior in the field of eye-tracking technology.